Nilai dan Fungsi Budaya Bakar Batu Dalam Relasi Lintas Suku di Pegunungan Tengah Papua: Sebuah Kajian Sosiologi Budaya - Abed Nego Tabuni (Jayapangus Press, 2023)
Bakar Batu is a deep culture folklore people in the central highlands of Papua who are firmly rooted in oral traditions. Bakar Batu has its own uniqueness because of the value content in it and how the local people live it. However, local people often see Bakar Batu only as a local tradition activity without ever knowing the value content in it, this has resulted in local people and this century's generation tending to be unable to see the value content in Bakar Batu, local cultural segregation occurs in the inability to read narratives local cultural values. This research aims to reveal the value and function contained in Bakar Batu in relation to strengthening inter-ethnic relations in the interior of the central mountains of Papua. This study will use ethnographic methods with a qualitative approach. Sources of data obtained through observation, interviews and literature review, the results of the discussion show that Bakar Baku has a complex value content that is a cultural representation of local communities and also immigrant communities formed from a process of learning together. So it can be concluded that Bakar Batu has a philosophical understanding and meaning about coexistence which is revived through oral tradition. Bakar Batu has economic, religious, political and social functions in the social order of the local community which strengthens shared identity.